Uric Acid Has Direct Proinflammatory Effects on Human Macrophages by Increasing Proinflammatory Mediators and Bacterial Phagocytosis Probably via URAT1 - Camilo P. Martínez-Reyes; Aarón N. Manjarrez-Reyna; Lucia A. Méndez-García; José A. Aguayo-Guerrero; Beatriz Aguirre-Sierra; Rafael Villalobos-Molina; Yolanda López-Vidal; Karen Bobadilla; Galileo Escobedo (Biomolecules, 2020)
The relationship of uric acid with macrophages has not been fully elucidated. We investigated the effect of uric acid on the proinflammatory ability of human macrophages and then examined the possible molecular mechanism involved. Primary human monocytes were differentiated into macrophages for subsequent exposure to 0, 0.23, 0.45, or 0.9 mmol/L uric acid for 12 h, in the presence or absence of 1 mmol/L probenecid. Flow cytometry was used to measure proinflammatory marker production and phagocytic activity that was quantified as a percentage of GFP-labeled Escherichia coli positive macrophages. qPCR was used to measure the macrophage expression of the urate anion transporter 1 (URAT1). As compared to control cells, the production of tumor necrosis factor-alpha (TNF-alpha), toll-like receptor 4 (TLR4), and cluster of differentiation (CD) 11c was significantly increased by uric acid. In contrast, macrophages expressing CD206, CX3C-motif chemokine receptor 1 (CX3CR1), and C-C chemokine receptor type 2 (CCR2) were significantly reduced. Uric acid progressively increased macrophage phagocytic activity and downregulated URAT1 expression. Probenecid—a non-specific blocker of URAT1-dependent uric acid transport—inhibited both proinflammatory cytokine production and phagocytic activity in macrophages that were exposed to uric acid. These results suggest that uric acid has direct proinflammatory effects on macrophages possibly via URAT1.